Effects of Combined 2,4-D and BAP Treatments on the Formation of Leaf-Derived Callus in Pogostemon cablin (Blanco) Benth. - Ira Puspaningtyas; Umi Mukholifah; Maitsa Adzro Fania; Desita Amalia Pratiwi; Reva Firstasa Asmara; Maulida Alfatikhatunnisa; Nurul Jadid (Universitas Sebelas Maret, 2025)
Pogostemon cablin (Blanco) Benth., a key source of patchouli oil (2.5 to 5% content), is widely used in the perfume and cosmetic industries but faces propagation challenges due to its time-consuming nature and susceptibility to pathogens. To overcome these limitations, in vitro techniques have been adopted to produce healthy and uniform seedlings efficiently. This study evaluated the effects of varying concentrations of 2,4-D (0 to 1.5 mg l-1) and BAP (0 to 1.5 mg l-1) on the in vitro induction of patchouli calli using axenic leaf explants cultured on Murashige and Skoog (MS) medium for 60 days. Growth parameters assessed included callus emergence time, morphological traits (texture and color), callogenesis percentage, organogenesis, and fresh callus weight. The results indicated that the combination of 2,4-D and BAP significantly influenced callogenesis, organogenesis, and callus morphology. The optimal combination (A0B3: 2,4-D 0 mg l-1 + BAP 1.5 mg l-1) achieved 100% callogenesis and organogenesis, with an average callus fresh weight of 0.25 g and an initiation time of 40.5 days. Calli exhibited a crumbly texture with a yellowish-white color, highlighting the role of auxin and cytokinin interactions in patchouli callus induction. These findings provide a foundation for scaling up in vitro patchouli oil production.